The Optimization of Hybrid Technology in Synchronous and Asynchronous Speaking Class - Agus Rofi'i; Herdiawan, Rama Dwika (Journal of Information System, Technology and Engineering, 2024)
In an era characterized by dynamic shifts in the field of education, the pursuit of effective teaching remains a prominent objective. This study investigates a novel methodology that integrates hybrid synchronous and asynchronous methods to enhance students' English language speaking skills in the context of English language instruction. This study commences by underscoring the significance of possessing proficient English-speaking skills. Dynamic learning encompasses a combination of real-time interactions and exercises that can be completed at different times. The objective of this study is to elucidate the perspectives of educators towards the integration of hybrid synchronous and asynchronous methodologies in the instruction of English language skills, specifically in the context of speaking classes. Educators in high school or vocational settings ought to use a blended approach to English language instruction, specifically in the context of speaking courses. The research employed a descriptive case study approach. The study incorporated participants who were engaged in semi-structured interviews that encompassed questionnaires administered with high rates of close-ended responses. The findings of the study indicate that there is a significant impact of social and psychological elements on teachers' proficiency in online communication. The ramifications of these findings are of great importance for educators in the field of English language instruction. The utilization of hybrid synchronous and asynchronous approaches has the potential to enhance students' oral communication abilities within the classroom setting. In summary, the hybrid approach to English instruction, encompassing both ongoing and non-ongoing components, involves the inclusion of proficient-speaking teachers and actively engaged students in speaking-focused sessions.